2015
DOI: 10.1177/0333102415572918
|View full text |Cite
|
Sign up to set email alerts
|

Headache neuroimaging: Routine testing when guidelines recommend against them

Abstract: Aims To determine the patient-level factors associated with headache neuroimaging in outpatient practice. Methods Using data from the 2007–2010 National Ambulatory Medical Care Surveys (NAMCS), we estimated headache neuroimaging utilization (cross sectional). Multivariable logistic regression was used to explore associations between patient-level factors and neuroimaging utilization. A Markov model with Monte Carlo simulation was used to estimate neuroimaging utilization over time at the individual patient-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 20 publications
2
35
0
3
Order By: Relevance
“…Recently, Choosing Wisely guidelines have focused on overuse by questioning the use of diagnostic neuroimaging in 2 highly prevalent neurologic conditions: headache and peripheral neuropathy. 2,3 Guideline discordant neuroimaging overuse appears to be common for headache 4,5 and peripheral neuropathy. [6][7][8] At the same time, underuse of neuroimaging in some highrisk headache patients 9 and diagnostic laboratory testing 10 in neuropathy patients likely exists.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Choosing Wisely guidelines have focused on overuse by questioning the use of diagnostic neuroimaging in 2 highly prevalent neurologic conditions: headache and peripheral neuropathy. 2,3 Guideline discordant neuroimaging overuse appears to be common for headache 4,5 and peripheral neuropathy. [6][7][8] At the same time, underuse of neuroimaging in some highrisk headache patients 9 and diagnostic laboratory testing 10 in neuropathy patients likely exists.…”
mentioning
confidence: 99%
“…Understanding the factors that mediate the appropriateness of testing between these 2 large health care systems has the potential to inform future efficiency initiatives. Many differences between the VA and Medicare exist and are potential contributory factors: the fixed resource VA environment, the centrality of primary care in the VA, 4 use of electronic medical records in the VA, 29 provider practice patterns, 30 and provider financial incentives. 31 Understanding which, if any, of these hypotheses account for the differences in appropriateness may inform future quality improvement initiatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we estimated that approximately $1 billion per year is spent on neuroimaging for outpatients for headache in the United States. 5,6 A separate group found similar neuroimaging utilization in headaches. 7 Likewise, high and rising neuroimaging utilization has been reported for patients with low back pain with high resulting costs.…”
Section: Discussionmentioning
confidence: 97%
“…To the Editor: In a recent paper published in Cephalalgia, the official journal of the American Headache Society, Callaghan et al [1] reported on information extracted from more than 50 million headache visits in the USA. This indicated that as many as 9.8% of patients with a diagnosis of migraines underwent neuroimaging -either magnetic resonance angiography or computed tomography.…”
Section: Neuroimaging In Migrainementioning
confidence: 99%